Microbial Communities and Nitrogen Transformation in Constructed Wetlands Treating Stormwater Runoff - Shirdashtzadeh, Maryam; Chua, Lloyd H. C.; Brau, Lambert (Frontiers in Water, 2022)
Microbial community play a vital role in nitrogen (N) removal in constructed wetlands (CWs). However, the lack of studies on microbial characteristics of wetland systems designed to treat stormwater demonstrates the importance of comprehensive investigation on microbial response to wetland fluctuations. Moreover, the observed inconsistency in N removal, and detected links between microbial shifts and wetland water level fluctuations is an area of research interest peculiar stormwater applications. This study surveyed nearly 150 publications to provide a summary and evaluation of N removal efficiency in different types of CWs where microbial community and their behavior have been correlated to regulating factors. Factors such as flow regime, plants, and physico-chemical properties (e.g., temperature, dissolved oxygen, pH, and nitrogen concentration) were found with significant influence on microbial diversity and compositions. Although many studies have analysed microbial N removal and responsible community, majority of them have conducted their studies in bioretention systems. Accordingly, some of the microbial pathways have not yet investigated in CWs designed for stormwater treatment. As such, it is suggested to investigate microbial community responsible for less investigated pathway, such as dissimilatory nitrate reduction to ammonium (DNRA) and comammox activity and their changes over dry-wet cycles in stormwater constructed wetlands. This information could assist engineers to take advantage of the presence of other N transforming community which could improve microbial diversity within wetland systems. Moreover, it is recommended to track microbial functional genes and their changes over wetland water fluctuation to develop an ecosystem with favourite condition for microbial pathways with higher N removal potential. In conclusion, the findings of the current literature review reinforce the importance of stormwater runoff treatments and implement of new design into CWs to enhance microbial activity and diversity leading to a wetland holistic development.